2007
DOI: 10.1021/bi700487q
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation Alters the Structure and Decreases the Stability of Human Lens βΑ3-Crystallin

Abstract: According to the World Health Organization, cataracts account for half of the blindness in the world, with the majority occurring in developing countries. A cataract is a clouding of the lens of the eye due to light scattering of precipitated lens proteins or aberrant cellular debris. The major proteins in the lens are crystallins and they are extensively deamidated during aging and cataracts. Deamidation has been detected at the domain and monomer interfaces of several crystallins during aging.The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 58 publications
(172 reference statements)
3
71
0
Order By: Relevance
“…Reported studies investigated the properties of deamidated properties or considered N to D substitution as a missense mutation. These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Reported studies investigated the properties of deamidated properties or considered N to D substitution as a missense mutation. These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is possible that by selectively replacing only those asparagines that are susceptible to deamidation, the thermotolerance of a protein could be improved. Although substantial information is available on deamidation-mediated loss in protein properties, that is, aggregation, stability, activity, most of the mutational studies were limited to site-directed mutagenesis with aspartate 7,23,24 and glutamate 7,25 and rarely glycine, alanine, and serine. 8,26 These studies have focused on explaining functional consequences of deamidation.…”
Section: -21mentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the observed loss of membrane segments gives the crystallins and fragments access routes to the ECS. Fourth, many of the changes to crystallins result in increased acidity (such as deamidation, Takata et al, 2007;Takemoto and Boyle, 1999); the increased negative charge causes the deposition onto the curved surfaces of AQP0 arrays because these have a net positive charge resulting from four surface positive charges per monomer (Harries et al, 2004). Fifth, the localization of deposits within the embryonic nucleus, where access to non-protein substances is limited, raises the probability that the deposits are derived from the most abundant material in the vicinity.…”
Section: Discussionmentioning
confidence: 99%